EORTC risk tables are more suitable for Chinese patients with nonmuscle-invasive bladder cancer than AUA risk stratification. Issue 36 (September 2018) - Wang, Hui; Ding, Weihong; Jiang, Guangliang; Gou, Yuancheng; Sun, Chuanyu; Chen, Zhongqing; Xu, Ke; Xia, Guowei
Abstract: Background: Patients with non-muscle-invasive bladder cancer (NMIBC) need accurate estimations of the risk of recurrence and progression. Physicians can offer individualized therapy after identifying high-risk tumors. In our study, we compared the applicability of European Organization for Research and Treatment of Cancer (EORTC) risk tables and American Urological Association (AUA) risk stratification in Chinese patients with NMIBC. Methods: We retrospectively studied 301 patients with NMIBC who underwent transurethral resection of bladder tumor (TURBT) between October 2000 and July 2009 at Huashan Hospital of Fudan University and analyzed their parameters. The recurrence and progression rates at 1 and 5 years postoperatively were calculated along with 95% confidence intervals. We compared them with results obtained from the EORTC risk tables and AUA risk stratification. P values <.05 were considered statistically significant. Results: The median patient age was 67 years (21–92 years) and the median follow-up duration was 46 months (2–151 months). We used EORTC risk tables to classify patients into 3 groups, depending on whether they suffered recurrence or progression after TURBT. Kaplan–Meier curves showed significant differences among the 3 recurrence-free survival (RFS) levels ( P < .0001, log-rank test) and among the 3 progression-free survival (PFS) levels ( P < .0001, log-rank test). AUA risk stratification showed the same results. Both classifications were suitable to predict recurrence and progression in Chinese patients. However, for high-risk patients in both series, Kaplan–Meier curves showed significant differences between RFS levels ( P < .0001, log-rank test) and between PFS levels ( P < .0001, log-rank test). EORTC risk tables were stricter and AUA was more sensitive in assigning patients to a high-risk group. Conclusion: EORTC risk tables are better than AUA risk stratification for predicting recurrence and progression in Chinese patients with NMIBC, especially among high-risk patients.